Embracing Technological Advancements: Impact on Academic Performance of School Teachers in Kathmandu - Hamal, Janga Bahadur; Dangol, Anista; Lama, Padam Bahadur (Marsyangdi Journal, 2024)
This paper aims to examine the effect of new technology adoption on employees' performance among school teachers in the Killagal-Nardevi area. In the study, technology adoption is an independent variable, and employee performance is a dependent variable. The adoption of new technology on employees' performance focuses on time management and performance targets for individual employees. The study has used descriptive, relational, and casual research designs considering the research objectives. The study is based on 106 valid responses, 76 percent, of the questionnaire distributed. A total of 29 questionnaires were not returned, and 5 were invalid due to incomplete filling up of the questionnaire. The study is based on the results obtained from descriptive, and inferential tools namely mean, median, standard deviation, correlation, and regression analysis. According to the findings of the study, technology adoption has a positive and significant relation to employee performance. Similarly, there is a positive and significant effect of technology adoption on teacher’s performance. The study, therefore, concludes that as technology tends to be advanced, employee performance is enhanced. Future studies can be conducted considering the broader area along with other variables.